Bornean Pygmy Elephant habitat usage of natural salt licks in Segaliud Lokan Forest Reserve. Issue 1 (1st June 2022) - Sompud, J; Adams, A Z; Hiew, S E; Maid, M; Kodoh, J; Mohd Sani, S; Goh, C; Jonalius, M; Baba, M
Abstract: Bornean pygmy elephant ( Elephas maximus borneensis ) is crucial in the forests ecosystem as it plays a vital role as a forest engineer. As such, it is crucial to conduct more research to contribute to the conservation of this species. This study examined the pygmy elephant usage of natural salt lick in Segaliud Lokan Forest Reserve (SLFR), also known as FMU19B. Salt lick is vital to maintain wildlife health. This study investigated the elephant's visitation frequency and examined its activity pattern in the natural salt lick area. A camera trap survey was conducted from November 2019 till August 2020. Four natural salt licks (C50SL, C56SL, C59SL and C60SL), and three non-salt licks (C50NSL, C56NSL, and C59&C60NSL) was selected. The data were analysed using descriptive and statistical analysis. The results show a higher visitation frequency at the salt lick area than the non-salt lick area (p<0.01). The salt lick at C59 was the most frequently visited by the elephant. The activity pattern displayed by the Bornean pygmy elephant shows a higher degree of nocturnal activity (73.3%). This information is essential for the timber concession forest managers to design the conservation work for the species in balancing with the timber extraction activity.